ANALISIS KUALITAS PEMERIKSAAN ANTENATAL CARE (ANC) MENURUT BUKU KIA - Noviana, Irma; Lumbanraja, Sarma N; Fitria , Aida (Jurnal Keperawatan Priority, 2023)
ANC services that have not fulfilled the 10 T standard are the cause of death. Many pregnant women were found to have incomplete records because laboratory tests for urine protein and complete tetanus immunization status were not carried out. This study aims to analyze the Analysis of Quality of Antenatal Services (ANC) according to the 2020 MCH Handbook. This type of quantitative research used the cross-sectional study approach which was carried out at the Sei Mencirim Health Center, Sunggal District, Deli Serdang from May to October 2022. A sample of 55 people was obtained using a purposive sampling technique. Data analysis used the Chi-Suare test and Logistic Regression. The results showed that there was a relationship between reliability, assurance, physical evidence, empathy, responsiveness, and the quality of antenatal care according to the 2020 MCH Handbook. The variable that was most related was the physical evidence variable. This study concludes that the quality of the ANC examination is according to the MCH handbook, but there are several indicators from the 10 T that have not been implemented. It is suggested to Puskesmas to optimize service standards appropriately and provide information according to services as well as provide adequate ANC service infrastructure and have optimal assessment accuracy.